Оцінка провідних індикаторів регуляторної політики держави у банківському секторі - Артеменко, Д.М. (Вісник економічної науки України, 2021)
У статті на основі узагальнення вітчизняного та міжнародного досвіду оцінки провідних індикаторів регуляторної політики держави у банківському секторі сформовані пропозиції щодо визначення фінансового стану і ризику банкрутства банку.
Запропоновано доповнити пруденційний банківський нагляд, що базується на відстеженні економічних нормативів окремих банків, моделями дискримінантного аналізу для комплексного визначення фінансового стану і ризику банкрутства банків.
Побудована еталонна матриця дискримінантного аналізу рівня фінансового стану та ступеня ризику настання банкрутства банку сприяє підвищенню якості фінансового визначення його ринкової вартості, яка є надійним індикатором для ухвалення обґрунтованих рішень з боку власників, менеджерів та клієнтів щодо підтримання його ефективного функціонування та подальшого стабільного розвитку.
Використання діапазону значень рівня ймовірності банкрутства, який є оберненою величиною до інтегрального показника фінансового стану банку, дозволяє більш диференційовано визначити класи банків за рівнем фінансового стану і групи банків за ризиком банкрутства.
Розроблена еталонна матриця, як вихідна складова методичного забезпечення комплексної фінансової оцінки ринкової вартості банків, дозволяє уникати помилок при обранні методичного підходу і методів розрахунку ринкової вартості конкретного банку та виявляти потенційні банки-банкрути для детальної переоцінки їх кредитних портфелів та портфелів цінних паперів. В статье на основе обобщения отечественного и международного опыта оценки основных индикаторов регуляторной политики государства в банковском секторе сформированы предложения по определению финансового состояния и риска банкротства банка.
Предложено дополнить пруденциальный банковский надзор, основанный на отслеживании экономических нормативов отдельных банков, моделями дискриминантного анализа для комплексного определения финансового состояния и риска банкротства банков.
Построенная эталонная матрица дискриминантного анализа уровня финансового состояния и степени риска наступления банкротства банка способствует повышению качества финансового определения его рыночной стоимости, которая является надежным индикатором для принятия обоснованных решений со стороны владельцев, менеджеров и клиентов по поддержанию его эффективного функционирования и дальнейшего стабильного развития.
Использование диапазона значений уровня вероятности банкротства, который является обратной величиной интегрального показателя финансового состояния банка, позволяет более дифференцированно определить классы банков по уровню финансового состояния и группы банков по риску банкротства.
Разработана эталонная матрица, как исходная составляющая методического обеспечения комплексной финансовой оценки рыночной стоимости банков, позволяет избегать ошибок при выборе методического подхода и методов расчета рыночной стоимости конкретного банка и выявлять потенциальные банки-банкроты для детальной переоценки их кредитных портфелей и портфелей ценных бумаг. The article, based on the generalization of domestic and international experience in assessing the leading indicators of regulatory policy in the banking sector, formed proposals to determine the financial condition and risk of bankruptcy of the bank.
It is proposed to supplement prudential banking supervision, based on tracking the economic standards of individual banks, with models of discriminant analysis for a comprehensive determination of the financial condition and risk of bankruptcy of banks.
The built-in reference matrix of discriminant analysis of the level of financial condition and the degree of risk of bankruptcy of the bank helps to improve the quality of financial determination of its market value, which is a reliable indicator for informed decisions by owners, managers and customers to maintain its effective functioning and further stable development.
The use of a range of values of the level of probability of bankruptcy, which is the inverse of the integral indicator of the financial condition of the bank, allows more differentiated determination of classes of banks by level of financial condition and group of banks by bankruptcy risk.
The developed reference matrix as a starting point of methodological support of comprehensive financial assessment of market value of banks avoids mistakes in choosing the methodological approach and methods of calculating the market value of a particular bank and identify potential bankrupt banks for detailed revaluation of their loan portfolios and securities portfolios.
Keywords: valuation, indicators, regulatory policy, probability of bankruptcy, financial condition, bank.

Bolotina Y., Shubna O., Byvsheva L. Features of Financing and Management of the Social Protection System in Ukraine. – Р. 120.
The article considers the features of financing and management of the social protection system of the population of Ukraine in a market economy. The directions of budget financing of the social sphere during 2010-2017 are determined. Activities for the social protection of the population are a mandatory component of any modern state. In general, social protection activities cover the area of material support and provision of social services to disabled people. The grouping of expenditures on social protection and social security by different categories according to the OECD database has been studied. Transfers in monetary and non-monetary forms to the population in the consolidated budget of Ukraine are analyzed. The dynamics of the population with average per capita equivalent total income per month, lower than the statutory subsistence level for 2010-2019, is analyzed. The modern problems of financing and management of the sphere of social protection of the population in Ukraine are revealed and the ways of their overcoming are outlined.